2018
DOI: 10.1128/jvi.02101-17
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase Siah-1 Suppresses Avian Reovirus Infection by Targeting p10 for Degradation

Abstract: Avian reovirus (ARV) causes viral arthritis, chronic respiratory diseases, retarded growth, and malabsorption syndrome. The ARV p10 protein, a viroporin responsible for the induction of cell syncytium formation and apoptosis, is rapidly degraded in host cells. Our previous report demonstrated that cellular lysosome-associated membrane protein 1 (LAMP-1) interacted with p10 and was involved in its degradation. However, the molecular mechanism underlying LAMP-1-mediated p10 degradation remains elusive. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…RNA interference with LAMP-1 reduced MDV titers and plaque sizes, highlighting the importance of LAMP-1 and MVBs in MDV replication and cell-to-cell spread. It has been suggested that avian LAMP-1 is involved in the degradation of the avian reovirus nonstructural p10 protein, involved in the induction of cell syncytium formation and apoptosis, through interacting with both p10 and the E3 ligase Siah-1 ( 31 , 32 ). We are currently examining whether LAMP-1 is also involved in the degradation of MDV viral proteins, which are required for the generation of infectious cell-free MDV.…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference with LAMP-1 reduced MDV titers and plaque sizes, highlighting the importance of LAMP-1 and MVBs in MDV replication and cell-to-cell spread. It has been suggested that avian LAMP-1 is involved in the degradation of the avian reovirus nonstructural p10 protein, involved in the induction of cell syncytium formation and apoptosis, through interacting with both p10 and the E3 ligase Siah-1 ( 31 , 32 ). We are currently examining whether LAMP-1 is also involved in the degradation of MDV viral proteins, which are required for the generation of infectious cell-free MDV.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that SMReV particles were sorted through early endosome to late endosome, finally disseminated to lysosome, in which the outer capsids of virus particles were disassembled by proteolytic cleavage. This disassembly may be significant for yielding metastable infectious subviral particle (ISVP) for productive infection (Zhang et al, 2006 ; Mainou and Dermody, 2011 ), otherwise may be due to the novel host defense mechanism of host to suppress virus infection through degradation to lead invalid infection (Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent CRISPR-mediated gene editing of MeE3L and infection with SACMV appears to induce increased expression of the MeE3L, suggesting that the interaction between the virus and MeE3L is based on recognition of the MeE3L's speci c base sequence. Previously, plant E3 ligases have been shown to be induced by viral infection (Lai et al, 2009;Czosnek et al, 2013;Chen et al, 2018) and plant defence elicitors (Libault et al, 2007;Sadanandom et al, 2012). The muted response of the T200 MeE3L to all treatments was expected given its nonsense mutation which silences the RING domain responsible for E3 ligase activity.…”
Section: Viral Activity and Gene Editing Of Mee3l Affect The Expressimentioning
confidence: 99%
“…Several viral proteins reportedly hinder E3 ligase function by encoding these E3 ligases in their viral genomes (Lai et al, 2009;Rosa-Diaz et al, 2013;Wang et al, 2013;Chen et al, 2018;Lozano-Duran and Bejarano, 2018). However, a blastn search for MeE3L homologs in the SACMV genome did not return any hits, thus ruling out the possibility that SACMV encodes a protein with E3 ligase activity as a strategy to target host proteins for degradation via the RNA silencing pathway.…”
Section: Sacmv's Interaction With a Tolerant Cassava Genotype Inducesmentioning
confidence: 99%